Efektifitas Teknik Distraksi Musik Klasik Mozart Untuk Mengurangi Nyeri Pada Pasien Post Operasi Fraktur - Fitra Mayenti; Yusnita Sari (Universitas Baiturrahim, 2020)
Most fractures are caused by traffic accidents with an estimated number of fractures in the world between 1 and 2.9 million with different age classifications. Each fracture will always undergo surgery followed by administering analgesics to reduce pain during the surgery. Non-pharmacological management to deal with pain consists of various physical treatment measures including skin stimulus, electrical nerve stimulation of the skin, acupuncture. The purpose of the study was to assess the effect of giving classical music mozart in reducing fracture pain in the Dahlia Room of Arifin Achmad Hospital Pekanbaru. Quasy Experiment Research Design, non randomized control group pretest postest design. The research sample was 30 respondents, with a sampling technique accidental sampling. The study was analyzed univariately and bivariately with the Wilcoxon and Man Whitney test. Testing the reduction in the degree of fracture pain in the control and experimental groups obtained the mean value of the experiment 6.71 post experiment 2.66 control value pre 6.35 and control post 6.48 with a value of ρ value 0.000 means that there is an influence of giving classical music mozart to fracture pain. Hopefully it can be used as a reference in providing mozart classical music distraction techniques to reduce pain in postoperative fracture patients